A method for preparing an interfacial reinforcement material for a fiber-reinforced polymeric prosthetic valve
Patent Information
- Application Number
- CN202611454828.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
但是,结构互锁和三维复合路线主要解决的是宏观应力分配和几何约束问题,并没有从根本上解决增强纤维与高分子基体之间的分子层级界面稳定性
[0072]1.本发明通过预复合使增强纤维相与高分子基体相形成连续贴合界面,再经热压处理在两相界面处形成界面过渡层,通过链段渗入、相互穿插及物理缠结作用强化界面结合,可有效抑制界面脱粘、分层及裂纹沿界面连续扩展,显著提升纤维增强高分子人工瓣膜的界面长期稳定性与疲劳耐久性。
Smart Images

Figure CN122955032A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomaterials technology for artificial heart valves, and relates to a method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves. Background Technology
[0002] Heart valve disease is a serious cardiovascular disease that severely endangers human health. Artificial heart valves are crucial implantable devices for treating severe valvular disease. Currently, mechanical valves and bioprosthetic valves are the main clinical applications, while polymeric artificial valves are rapidly developing. Mechanical valves have good durability but are prone to thrombosis, requiring patients to undergo long-term anticoagulation. Bioprosthetic valves have good blood compatibility but are susceptible to calcification, tearing, and structural failure. Polymeric artificial valves offer advantages such as controllable processing, lower cost, adjustable physicochemical properties, and no risk of animal-derived immune responses, making them a key research direction for next-generation artificial valves.
[0003] Commonly used materials for polymeric artificial valves include polyurethane elastomers, polycarbonate elastomers, polyester elastomers, polyolefin elastomers, siloxane elastomers, fluoropolymers, and copolymers or blends of the above materials. Artificial heart valves face extremely stringent mechanical challenges in vivo. The leaflets endure tens of millions of bending and stretching cycles annually under long-term, high-frequency, cyclic alternating loads and the coupling effect of fluid shear. In such extreme dynamic service environments, a single polymeric matrix material is highly susceptible to microscopic damage due to accumulated dynamic fatigue, and irreversible flow creep and localized thinning are prone to occur during high-pressure differential closure, leading to valve insufficiency or premature structural failure. Therefore, introducing a reinforcing fiber composite structure is a crucial means to ensure the long-term dynamic durability of the valve. By introducing a high-modulus reinforcing fiber network into the polymeric matrix, the reinforcing fiber phase bears the peak load and provides the structural framework, while the polymeric matrix phase maintains the required flexibility and opening / closing response of the leaflets. Both phases perform their respective mechanical functions, thereby significantly alleviating fatigue damage to the matrix and inhibiting or delaying its long-term creep process. More importantly, this composite structure changes the failure mode where local damage to a single material leads to overall failure, giving the material a multi-level energy dissipation mechanism. When encountering microcrack initiation, it can suppress catastrophic tearing through reinforced fiber bridging, thereby improving its long-term fatigue durability.
[0004] However, the effective realization of the aforementioned fiber-reinforced composite effect is highly dependent on the stability of the interface between the fiber-reinforced phase and the polymer matrix phase under long-term high-frequency cyclic loading. The key technological bottleneck in artificial valves lies not only in improving initial strength but also in whether the interface can withstand the rigorous test of hundreds of millions of alternating stresses. In fiber-reinforced composites, the interface is not merely a geometric contact boundary but a core channel for stress transfer and energy dissipation between the two phases. If the interfacial bonding between the fiber-reinforced phase and the polymer matrix phase is insufficient, the load generated in the matrix cannot be continuously and effectively transferred to the fiber-reinforced phase, and the reinforcing effect of the high-modulus fiber skeleton cannot be fully realized. Simultaneously, stress concentration, microvoids, and local slippage can occur at the interface due to differences in modulus and deformation mismatch between the two phases, thus evolving into preferential pathways for crack initiation and propagation. Especially for fiber-reinforced polymer artificial valves with limited thickness, subjected to prolonged exposure to hot and humid blood flow and high-frequency opening and closing, interface debonding, delamination, or fiber pull-out not only weakens the overall load-bearing capacity of the composite material but also leads to decreased leaflet flexibility, abnormally increased local stress, and ultimately induces tearing, increased regurgitation, and structural failure, seriously threatening their long-term fatigue durability. Therefore, improving the stability of the reinforcing fiber / polymer matrix interface is not a secondary optimization of the reinforcing fiber structure but a key factor in determining whether the reinforcement mechanism can truly translate into the long-term durability and service safety of fiber-reinforced polymer artificial valves.
[0005] In existing technologies, the methods for strengthening the interface between reinforcing fibers and polymer matrices can be mainly categorized as follows:
[0006] The first category includes direct impregnation, hot pressing, lamination, and composite routes with reinforcing fiber skeletons. Existing technologies widely employ methods such as dip coating, solution lamination, vacuum infiltration, hot pressing after preforming, simple lamination, and impregnation after electrospinning skeletons to combine reinforcing fibers with polymer matrices to form composite valve materials [Reference 1: Materials and manufacturing perspectives in engineering heart valves: a review[J]. Materials Today Bio,2020, 5: 100038; Reference 2: Hydrogel-polyurethane fiber composites with enhanced microarchitectural control for heart valve replacement[J]. Journal of Biomedical Materials Research Part A, 2024, 112(4): 586-599]. Among these methods, hot pressing, hot melting, compaction, and melt infiltration can, to a certain extent, improve the filling degree and coating continuity of the reinforcing fiber network in the matrix. However, most of these approaches remain at the level of "composite molding" or "compaction densification," which usually only allows the polymer matrix to enter the pores of the reinforcing fiber and adhere to the surface of the reinforcing fiber. The interface still mainly relies on physical wetting, flow coating and limited mechanical interlocking to maintain, making it difficult to form a stable interfacial bond at the molecular level.
[0007] The second category includes surface activation, wet chemical modification, coupling bridging, graft compatibility, and intermediate layer construction routes. A large number of general composite material studies have proposed routes such as surface activation, wet chemical modification, coupling bridging, graft copolymerization, compatibility, intermediate layer and coating construction, including plasma, corona, ultraviolet / ozone, acid-base oxidation, silane coupling agents, small molecule bridging agents, grafted segments, compatibility agents, intermediate transition layers, adhesive layers and functionalized interface layers [Reference 3: Methods and models for fibre-matrix interface characterisation in fibre-reinforced polymers: a review[J]. International Materials Reviews, 2023, 68(8): 1245-1319; Reference 4: Interfacial interlocking of carbon fiber-reinforced polymercomposites: a short review[J]. Polymers, 2025, 17(3): 267]. In research on materials related to artificial valves, approaches such as hydrogel / polyurethane fiber composites can be viewed as improving the microstructure and local interfacial environment by constructing transition layers or third-phase composite layers. However, while these approaches can improve initial adhesion or short-term interfacial strength, they often require additional surface treatment steps, chemical reaction reagents, coupling molecules, initiators, catalysts, or intermediate layer materials. For fiber-reinforced polymer artificial valves subjected to long-term blood contact, prolonged damp heat, and long-term high-frequency cycling, these additional interfacial layers or surface chemical structures may bring several risks. First, the modification depth is often limited to the surface of the reinforcing fiber, and the treatment effect may decay over time, and is greatly affected by the uniformity of treatment and batch fluctuations. Second, over-treatment may cause surface embrittlement of the reinforcing fiber, increase defects, or reduce the original mechanical properties, affecting the load-bearing capacity of the reinforcing fiber. Third, the additional small molecules, intermediate layers, or third-phase interfaces may age, peel off, or detach during long-term service, becoming new sources of crack initiation. Fourth, improper control of the thickness and continuity of the interlayer may also affect the leaflet thickness, flexibility, opening and closing response, and hemodynamic performance, impairing the compliant opening and closing function of the polymer matrix. Therefore, interface modification methods in general composite materials cannot be automatically applied to the specific scenario of fiber-reinforced polymer artificial valves.
[0008] The third category is the composite approach of roughening interlocking, three-dimensional networks, and macroscopic structures. Existing technologies improve the anchorage of the matrix in the reinforcing fiber network and disperse interfacial stress by increasing the reinforcing fiber content, changing the orientation, increasing the number of layers, constructing woven / knitted / nonwoven networks, introducing three-dimensional interpenetrating structures, and designing interfacial interlocking structures [Reference 5: Structural reinforcements as a strategy toward durable polymeric heart valves[J]. Cell Reports Physical Science, 2024, 5(3): 101870]. These methods can improve the macroscopic load-bearing path and local geometric anchorage conditions, which has a certain positive significance for improving initial strength and crack propagation resistance. However, structural interlocking and three-dimensional composite approaches mainly solve the problems of macroscopic stress distribution and geometric constraints, but do not fundamentally solve the molecular-level interface stability between the reinforcing fiber and the polymer matrix. If the interface itself is still not sufficiently bonded, the higher the volume fraction of reinforcing fibers, the larger the interface area, and the more complex the hierarchical structure, the more potential debonding paths and stress concentration areas there will be. Cracks may still preferentially propagate along the interface, and long-term fatigue durability cannot be guaranteed. In other words, structural reinforcement is not the same as interface reinforcement, and geometric interlocking is not the same as a long-term durable interface force transmission channel.
[0009] Therefore, there is an urgent need for an interface reinforcement method suitable for fiber-reinforced polymer artificial valves, which can improve the interfacial stability, crack propagation resistance, and long-term fatigue durability of fiber-reinforced polymer artificial valves while maintaining the respective mechanical functions of the reinforcing fibers and polymer matrix. Summary of the Invention
[0010] The purpose of this invention is to address the problems existing in the prior art and to provide a method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves.
[0011] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0012] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, the specific process of which is as follows:
[0013] First, the reinforcing fiber phase and the polymer matrix phase are pre-composite, so that the polymer matrix phase enters the pores and / or surface gaps of the reinforcing fiber phase, thereby forming a continuous bonding interface between the reinforcing fiber phase and the polymer matrix phase. There are no continuous unwetted areas, continuous bubble layers or through pores between the two that block the penetration of the polymer matrix phase and the formation of the interface transition layer.
[0014] Subsequently, the pre-composite material is subjected to hot pressing treatment, which softens, melts or activates chain segments at the interface of the polymer matrix phase and penetrates into the surface of the reinforcing fiber phase. At the same time, the reinforcing fiber phase is activated only in the surface area, locally swollen or locally micro-melted, while the internal main body of the reinforcing fiber phase maintains a continuous structure.
[0015] During the hot pressing process, an interfacial transition layer (with a thickness of 10 nm-20 μm, preferably 50 nm-5 μm, and more preferably 100 nm-2 μm) is formed at the interface between the reinforcing fiber phase and the polymer matrix phase. The interfacial transition layer includes a region where polymer matrix phase segments penetrate into the surface of the reinforcing fiber phase, a region where reinforcing fiber phase surface segments interpenetrate with polymer matrix phase segments, and an interfacial bonding region formed by physical entanglement and / or intermolecular interactions. This interfacial transition layer can be verified by observing the absence of obvious interfacial voids using scanning electron microscopy, testing the hardness gradient transition region using atomic force microscopy, detecting the characteristic peak shift using Fourier transform infrared spectroscopy, and detecting the thermal transition transition region using differential scanning calorimetry or dynamic thermomechanical analysis.
[0016] The hot pressing temperature is set above the softening temperature, melting temperature or chain segment activation temperature of the polymer matrix phase, so that the polymer matrix phase preferentially undergoes interfacial penetration, while being lower than the temperature at which the reinforcing fiber phase undergoes overall melting, loses its continuous fiber morphology or loses its continuous load-bearing structure.
[0017] The hot pressing pressure is sufficient to maintain the continuous adhesion of the interface and promote the penetration of the polymer matrix phase, but not enough to cause the overall compaction and collapse of the reinforcing fiber phase or excessive loss of the polymer matrix phase.
[0018] The effective heat preservation time of hot pressing is the duration that can ensure the formation of an interfacial transition layer at the interface between the reinforcing fiber phase and the polymer matrix phase, but is insufficient to cause substantial thermal degradation or interfacial embrittlement of the material.
[0019] By matching and controlling the hot pressing temperature, pressure, holding time and the thermal conductivity of the material, the formation state of the interface transition layer can be precisely controlled, avoiding simple physical bonding or overall melting and collapse of the reinforcing fiber phase.
[0020] Finally, cooling is performed under pressure while maintaining continuous bonding between the interfaces to fix the interface transition layer and obtain the interface reinforcement material.
[0021] The cooling termination temperature is the temperature at which the chain segment movement at the interface between the polymer matrix phase and the reinforcing fiber phase is significantly restricted, thereby fixing the interface transition layer.
[0022] The cooling pressure is sufficient to maintain the continuous adhesion between the reinforcing fiber phase and the polymer matrix phase interface during the cooling process and to inhibit interface separation or regeneration of interface pores caused by thermal shrinkage differences, but not sufficient to cause the reinforcing fiber phase structure to collapse, the polymer matrix phase to be over-extruded, or the material thickness to change unacceptably.
[0023] Cooling time is the duration required for the material to cool from a hot-pressed state to the cooling termination temperature, and this duration is sufficient to fix the interface transition layer and reduce residual thermal stress at the interface, but not so short as to cause the pressure to be released before the interface is stable.
[0024] The cooling atmosphere is one that will not cause substantial oxidative degradation, thermo-oxidative aging, or deterioration of interfacial properties in the reinforcing fiber phase and the polymer matrix phase during the cooling process.
[0025] This invention does not rely on complex chemical grafting or exogenous interfacial coupling agents. It primarily achieves interfacial reinforcement structures through material compatibility selection and thermal processing window control, which helps reduce the risk of residual reagents and improves batch production stability. This method achieves preferential interfacial penetration of the polymer matrix phase, interpenetration of the reinforcing fiber surface layer, and maintenance of a continuous load-bearing structure in the internal matrix through material structure matching, modulus difference regulation, thermal transformation behavior matching, and precise control of the hot-pressing window. This solves the technical problem of existing technologies that struggle to simultaneously achieve interfacial bonding strength, leaflet flexibility, and long-term fatigue durability.
[0026] As a preferred technical solution:
[0027] The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, as described above, wherein the reinforcing fiber phase and the polymer matrix phase satisfy at least one of the following structural matching conditions:
[0028] a. Both contain at least one identical chemical structural unit in their molecular chains;
[0029] b. Both contain complementary chemical structural units that can form hydrogen bonds, dipole interactions, or ion-dipole interactions with each other;
[0030] c. Both contain similar soft segments, similar hard segments, or similar crystalline segments that can undergo local mutual dissolution, segment diffusion, or crystalline region intercalation under hot pressing;
[0031] The chemical structural units are selected from urethane bonds, urea bonds, ester bonds, amide bonds, ether bonds, carbonate bonds, siloxane segments, fluorocarbon segments, olefin segments, aromatic segments, or combinations thereof.
[0032] Through the above structural matching, the polymer matrix phase can be softened, melted or activated at the interface and penetrate into the surface of the reinforcing fiber phase during hot pressing. At the same time, the reinforcing fiber phase is activated only in the surface area, locally swollen or locally micro-melted, while the internal main body of the reinforcing fiber phase maintains a continuous structure.
[0033] The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, as described above, has a tensile modulus of the reinforcing fiber phase that is higher than that of the polymer matrix phase.
[0034] This configuration allows the reinforcing fiber phase to bear the main load and crack bridging role in the composite valve leaflet, while the polymer matrix phase mainly bears the role of compliant deformation and interfacial stress transfer. It also allows the already formed interfacial transition layer to more effectively perform the functions of force transmission, crack prevention, and fatigue resistance under long-term cyclic loading, thus meeting the application goals of "reinforcement" and "compliant opening and closing" in artificial valve scenarios.
[0035] The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves as described above, wherein the tensile modulus of the reinforcing fiber phase is 1.5-20 times that of the tensile modulus of the polymer matrix phase, more preferably 2-10 times, and even more preferably 2-6 times.
[0036] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valves described above has the following characteristics: the glass transition temperature Tg of the hard segment of the surface chain of the reinforcing fiber phase is higher than the softening temperature Ts of the polymer matrix phase, which dominates the interfacial penetration and chain diffusion; and the morphology retention ability of the reinforcing fiber phase under hot pressing is higher than that of the polymer matrix phase.
[0037] This configuration facilitates the preferred interface formation method during hot pressing, where the polymer matrix phase softens preferentially and penetrates into the interface, the reinforcing fiber phase is mainly activated in the surface area, and the overall skeleton remains continuous. This helps to strengthen the interface while avoiding the overall collapse of the reinforcing fiber phase or the destruction of the load-bearing structure.
[0038] In the preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valves as described above, the difference between Tg and Ts is 5-120℃, more preferably 10-80℃, and even more preferably 15-60℃.
[0039] As described above, a method for preparing an interfacial reinforcement material for fiber-reinforced polymer artificial valves involves a reinforcing fiber phase and a polymer matrix phase exhibiting different but compatible segment mobility under hot pressing. This allows polymer matrix phase segments to diffuse towards the surface of the reinforcing fiber phase, enabling surface segments of the reinforcing fiber phase to participate in interfacial interpenetration, while the internal bulk of the reinforcing fiber phase maintains a continuous reinforcement structure.
[0040] This arrangement promotes the interpenetration and physical entanglement of interface segments, limits the interface effect to the surface of the reinforcing fiber, and avoids overall softening, overall flow, or damage to the load-bearing skeleton of the reinforcing fiber.
[0041] As described above, in the preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valves, there is no continuous non-diffusion barrier layer on the surface of the reinforcing fiber phase; if there is a treatment layer, coating or intermediate layer on the surface of the reinforcing fiber phase, the treatment layer, coating or intermediate layer is compatible with the polymer matrix phase under hot pressing conditions, and allows matrix chain segments and / or surface chain segments of the reinforcing fiber phase to migrate across the interface.
[0042] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valves described above allows the surface chain segments of the reinforcing fiber phase and the chain segments of the polymer matrix phase involved in the formation of the interface transition layer to undergo cross-interface migration under hot-pressing conditions. Furthermore, the content of residual solvent, moisture, adsorbed gas, and other volatile substances in the pre-composite structure is controlled within a range that will not form continuous bubbles, continuous pores, or gas escape channels at the interface.
[0043] The method described above for preparing an interface reinforcement material for fiber-reinforced polymeric artificial valves, wherein the reinforcing fiber phase material is a bio-stable polymeric fiber suitable for polymeric artificial valves or long-term implanted elastic composite materials, and the range of options includes, but is not limited to, the specific types listed below. Other options include polyether ester fibers, polyimide fibers, polyether ether ketone fibers, polyarylate fibers, polylactic acid fibers, polycaprolactone fibers, copolymer fibers of the above materials, or blended fibers. The polymeric matrix phase material is an elastic or... Thermoplastic polymer materials, including but not limited to the specific types listed below, may also be selected from siloxane elastomers, styrene block copolymers, polyether ester elastomers, polycaprolactone materials, polylactic acid materials, copolymers or blends of the above materials; the specific material combinations and corresponding hot pressing parameters are as follows: the reinforcing fiber phase material is poly(carbonate-urea-polyurethane), the polymer matrix phase material is siloxane-polycarbonate polyurethane, the hot pressing temperature is 190-210℃, the hot pressing pressure is 5-10MPa, and the effective hot pressing holding time is 3-15min;
[0044] Alternatively, the reinforcing fiber phase material is polycarbonate-type polyurethane, the polymer matrix phase material is polyether ester block copolymer elastomer, the hot pressing temperature is 150-188℃, the hot pressing pressure is 2-12MPa, and the effective hot pressing holding time is 1-15min.
[0045] Alternatively, the reinforcing fiber phase material is polyurethane, the polymer matrix phase material is polyurethane elastomer, the hot pressing temperature is 160-220℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min.
[0046] Alternatively, the reinforcing fiber phase material is polyester, the polymer matrix phase material is polyester elastomer, the hot pressing temperature is 140-210℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min.
[0047] Alternatively, the reinforcing fiber phase material is polyamide, the polymer matrix phase material is polyamide elastomer, the hot pressing temperature is 160-240℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min.
[0048] Alternatively, the reinforcing fiber phase material is polyolefin, the polymer matrix phase material is polyolefin elastomer or polyolefin, the hot pressing temperature is 120-180℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min.
[0049] Alternatively, the reinforcing fiber phase material is a fluoropolymer, the polymer matrix phase material is a fluoroelastomer or fluoropolymer, the hot pressing temperature is 180-280℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing time is 1-30min.
[0050] Alternatively, the reinforcing fiber phase material is polycarbonate, the polymer matrix phase material is polycarbonate elastomer, the hot pressing temperature is 170-240℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min.
[0051] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valves described above, wherein the fiber diameter of the reinforcing fiber phase is 50 nm-100 μm.
[0052] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valves as described above, wherein the reinforcing fiber phase is a nanofiber network (including but not limited to single-layer oriented fiber network, multi-layer oriented fiber network, three-dimensional interpenetrating fiber network, electrospun membrane, and air-jet electrospun membrane), with a fiber diameter of 50-1000 nm; or, the reinforcing fiber phase is a micron-sized filament, fabric (including but not limited to woven fabric, knitted fabric, and nonwoven fabric) or braided skeleton, with a fiber diameter of 1-100 μm.
[0053] The aforementioned reinforcing fiber phase can be prepared by electrospinning, air-jet electrospinning, melt spinning, braiding, knitting, woven, or nonwoven processes. When using solution spinning, the mass fraction of the spinning solution is preferably 1wt%-20wt%, more preferably 3wt%-10wt%. The nanofiber network is preferably prepared by air-jet electrospinning, and the fiber diameter is preferably 300-500nm, which can form a three-dimensional fiber structure with open pores. The multilayer oriented fiber network can construct an orientation gradient structure by programmatically adjusting the preparation process parameters, and the thickness ratio is preferably 45:35:20, so that the final interface reinforcement material has orthogonal anisotropy and nonlinear mechanical response similar to natural valves.
[0054] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valve as described above, wherein the volume fraction of the reinforcing fiber phase in the interface reinforcement material is 5%-80%.
[0055] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valve described above has a thickness of 30-1000 μm. The specific thickness can be adjusted according to the application scenario. For example, when used for aortic valve, pulmonary valve or transcatheter valve leaflet, the thickness is 150-350 μm.
[0056] When artificial valves are made from this interface-enhanced material, the material can be cut or thermoformed into leaflets and then assembled with a valve frame, skirt, or support structure to obtain the finished product. Applicable types of artificial valves include surgical replacement valves, transcatheter aortic valves, pulmonary valves, mitral valve leaflet repair materials, or other polymer valves that withstand cyclic opening and closing loads.
[0057] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valves described above includes the following pre-composite process: immersing the reinforcing fiber phase in a polymer matrix phase solution, dispersion, or melt, followed by vacuum degassing and infiltration treatment, and then removing the solvent to obtain a pre-composite preform.
[0058] The mass fraction of the polymer matrix phase solution is preferably 2wt%-25wt%, more preferably 5wt%-15wt%, and even more preferably 8wt%-12wt%. The solvent for the polymer matrix phase solution can be selected according to the polymer matrix phase material, such as hexafluoroisopropanol, dimethylformamide, tetrahydrofuran, dimethylacetamide, dichloromethane, toluene, cyclohexane, water, or a mixture thereof. During the impregnation process, the material thickness and polymer matrix phase content can be controlled by means of a doctor blade, pressure roller, lifting, spin coating, calendering, or molding. The vacuum degree for vacuum degassing is preferably 50-500 mbar, more preferably 100-200 mbar. The processing time is preferably 1-60 min, more preferably 5-30 min. Solvent removal can be achieved by solvent evaporation at room temperature or 30-80℃. If necessary, multiple impregnation and drying operations can be performed to control the volume fraction of the reinforcing fiber phase, the matrix filling degree, and the material thickness.
[0059] The preparation method of the interface reinforcement material for fiber-reinforced polymer artificial valve as described above, wherein the 90° peel strength of the interface reinforcement material is 2.6-3.6 N / mm and the interfacial peel strength is 3.5-5.1 N / mm, under the same conditions of reinforcing fiber phase material, polymer matrix phase material, fiber volume fraction and material thickness, compared with the control material without the hot-pressing interface reinforcement treatment, at least one of the 90° peel strength and interfacial peel strength is increased by more than 20%;
[0060] During tearing, fracture, or fatigue loading, the crack propagation path of the interface-reinforced material no longer extends continuously along the interface between the reinforcing fiber phase and the polymer matrix phase. Instead, it exhibits at least one of the following: crack deflection, crack passivation, fiber bridging, and matrix / fiber co-fracture. The corresponding fracture surface shows a reduction in fiber pull-out length and interface debonding area, with a higher proportion of common fracture region compared to the control material without hot pressing treatment. Under cyclic loading, the interface transition layer can alleviate the strain discontinuity between the reinforcing fiber phase and the polymer matrix phase, reducing the initiation of microcracks at the interface. When cracks encounter oriented fibers, energy dissipation can be achieved through deflection, bridging, and passivation, thereby reducing the crack propagation rate. The above macroscopic mechanical characteristics and crack propagation behavior can serve as auxiliary criteria for determining the formation of an interface transition layer at the interface.
[0061] The tearing energy of interface-reinforced materials is 63-112 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under the same conditions of reinforcing fiber phase material, polymer matrix phase material, fiber volume fraction and material thickness, compared with the control material without the hot-pressing interface reinforcement treatment, at least one of the tearing work, fracture energy, critical energy release rate or fatigue life is improved; compared with ordinary dip-coated composite materials, the tearing work, critical energy release rate or fatigue threshold can be significantly improved, making the leaflets less prone to tearing during long-term opening and closing.
[0062] Fiber-reinforced polymer artificial valves made from interface-reinforced materials, after 400 million cycles in accelerated fatigue testing conditions at 37°C saline, 20Hz frequency, and a closure pressure differential greater than 100 mmHg, showed no macroscopic tearing, significant delamination, or obvious interface debonding of the leaflets. During subsequent pulsating flow testing after accelerated fatigue testing, the changes in average transvalvular pressure differential, regurgitation percentage, and effective valve orifice area were all less than 10%, and crack propagation did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase. The leaflets made from this material balance strength and flexibility, reduce valve root stress concentration, and maintain stable hemodynamic parameters such as effective valve orifice area, transvalvular pressure differential, and regurgitation percentage under long-term cyclic loading. The prepared interface-reinforced material also exhibits good in vitro biocompatibility, blood compatibility, environmental stability, and anti-calcification properties, with no significant cytotoxicity, minimal platelet adhesion and aggregation, high mechanical property retention after long-term aging, and lower calcium deposition after in vivo implantation compared to traditional bioprosthetic valve materials.
[0063] In existing technologies, the evaluation of interface enhancement effects mostly focuses on initial interfacial adhesion strength, static tensile strength, or short-term mechanical properties, lacking long-term fatigue verification under the real-world service environment of artificial valves. In the field of artificial valves, relevant device testing standards also emphasize that polymer valves must undergo long-term fatigue, deformation stability, and real-world loading verification, and cannot be judged solely based on initial strength. However, most existing evaluation methods lack sufficient proof of interfacial stability under long-term damp heat, oxidation, pulsating flow erosion, and hundreds of millions of high-frequency cyclic fatigue conditions. Therefore, simply increasing initial peel strength or static tensile strength is insufficient to prove that an interface enhancement method is suitable for the long-term service of artificial valves.
[0064] While existing research has revealed the superior performance of natural fiber-soft matrix systems under long-term fatigue conditions, the subjects of these studies are natural biological tissues, which cannot be directly applied to synthetic material systems. Chemically fixed bovine pericardium exhibits excellent defect-insensitive fatigue resistance under cyclic tensile conditions, but it does not provide selection rules or process windows for interface reinforcement materials applicable to synthetic reinforcing fiber-polymer matrix systems. Therefore, while the insights from natural tissues are important, they cannot be directly translated into interface reinforcement schemes for synthetic material systems.
[0065] In summary, existing evaluation indicators for the long-term stability of fiber-reinforced polymer artificial valve interfaces are inadequate. Most existing indicators focus on initial strength, short-term mechanical properties, or conventional conditions, lacking a unified evaluation standard for systematically assessing interface stability, crack propagation resistance, and long-term fatigue durability under real-world service environments. Therefore, this invention establishes a set of interface long-term stability evaluation indicators capable of reflecting the stringent requirements of artificial valves undergoing hundreds of millions of cycles of service, to reliably determine whether the interface reinforcement effect meets practical application needs.
[0066] To further clarify the mechanism of action, material selection logic, preparation process, and performance improvement effects of this invention, the following description is provided in conjunction with the accompanying drawings:
[0067] from Figure 1 The difference in the mechanism of insufficient interfacial bonding between the reinforcing fiber phase and the polymer matrix phase compared to hot-pressed interfacial reinforcement is evident. Without a stable interfacial transition layer, the polymer matrix phase primarily acts as a physical coating of the reinforcing fiber phase, resulting in micropores and localized debonding at the interface, leading to stress concentration. Under cyclic loading, cracks easily propagate continuously along the interface between the reinforcing fiber phase and the polymer matrix phase, accompanied by delamination, fiber pull-out, and localized tearing, thus interrupting interfacial stress transmission. After temperature-, pressure-, and time-controlled hot-pressing, polymer matrix phase segments diffuse into the surface of the reinforcing fiber phase. The surface segments of the reinforcing fiber phase interpenetrate with the polymer matrix phase segments, forming a continuous interfacial transition layer through physical entanglement and intermolecular interactions. This interface maintains continuous stress transmission, causing crack deflection and passivation during propagation, and dissipating fracture energy through fiber bridging, thereby inhibiting delamination, interfacial debonding, and localized tearing.
[0068] from Figure 2This reveals the material selection rules for the reinforcing fiber phase and the polymer matrix phase, as well as the formation principle of the interfacial transition layer. Material selection needs to be considered from three dimensions: chemical structure matching, mechanical property matching, and thermal transformation behavior matching. In terms of chemical structure, the reinforcing fiber phase segments and the polymer matrix phase segments should have matching chemical structural units to form hydrogen bonds, dipole interactions, local compatibility, crystalline region intercalation, and other intermolecular interactions. In terms of mechanical properties, the reinforcing fiber phase should have a higher tensile modulus than the polymer matrix phase to bear the main load and play a fiber bridging role, while the polymer matrix phase maintains its flexible deformation ability and is responsible for interfacial stress transfer. In terms of thermal transformation behavior, the polymer matrix phase should be preferentially softened or melted, while the reinforcing fiber phase should only be activated, locally swollen, or locally micro-melted in the surface area, while the internal bulk of the reinforcing fiber phase still maintains a continuous reinforcing structure. Based on this, the formation process of the interface transition layer is as follows: the polymer matrix phase is preferentially softened, the surface chain segments of the reinforcing fiber phase are activated, and then an interface transition layer is formed within the hot pressing window, which is composed of polymer matrix phase chain segment diffusion, reinforcing fiber phase surface chain segment interpenetration, physical entanglement, and intermolecular interaction. Ultimately, it achieves enhanced interface bonding, continuous stress transmission, crack deflection / passivation / bridging, crack propagation resistance, and improved long-term fatigue durability, taking into account the strength and flexibility required by artificial valves.
[0069] from Figure 3 This paper presents the complete preparation process and interface evolution of the fiber-reinforced polymer artificial valve interfacial reinforcement material. First, the reinforcing fiber phase is prepared by air-jet electrospinning, forming a reinforcing fiber network with open pores. Second, the reinforcing fiber skeleton structure is determined through fiber layup, orientation, and areal density control. Next, the polymer matrix phase is prepared into a solution, and the reinforcing fiber network is immersed in the polymer matrix phase solution. Degassing and permeation are simultaneously performed under vacuum conditions, allowing the polymer matrix phase to enter the pores of the reinforcing fiber network and the interstices on the fiber surface. Subsequently, a pre-composite membrane is obtained by removing the solvent and pre-forming. Then, temperature-controlled hot pressing is performed under set hot pressing temperature, hot pressing pressure, and effective holding time, allowing the polymer matrix phase to permeate into the surface of the reinforcing fiber phase and form an interfacial transition layer, while preventing the reinforcing fiber phase from melting, collapsing, or losing its continuous load-bearing structure. After hot pressing, cooling is performed under maintained pressure to fix the interfacial transition layer. Finally, the valve is formed according to the structural and dimensional requirements of the artificial valve leaflet, resulting in a fiber-reinforced polymer artificial valve. From the perspective of interface evolution, the interface in the preforming stage is mainly a physical coating interface, while after hot pressing, an interface transition layer is formed that includes chain segment diffusion, physical entanglement and intermolecular interactions.
[0070] from Figure 4The results show the differences in interface failure modes and stress transfer paths of materials under cyclic loading before and after hot-pressing interface reinforcement treatment. In materials without hot-pressing interface reinforcement treatment, the polymer matrix phase and reinforcing fiber phase are mainly physically coated, with interfacial voids, local debonding, and discontinuous bonding at the interface. Under cyclic loading, stress transfer is interrupted, and cracks easily propagate along the interface between the reinforcing fiber phase and the polymer matrix phase, resulting in delamination, fiber pull-out, and localized tearing. After temperature-, pressure-, and time-controlled hot pressing interface reinforcement treatment, a continuous interface transition layer and a local interdiffusion region are formed at the interface. This includes the diffusion of polymer matrix phase segments to the surface of the reinforcing fiber phase, the interpenetration and physical entanglement of the surface segments of the reinforcing fiber phase and the polymer matrix phase segments, and intermolecular interactions. This interface transition layer enables stress to be continuously transferred to the reinforcing fiber phase and dissipates fracture energy through fiber bridging, crack deflection, and crack passivation. It promotes the synergistic load-bearing of the reinforcing fiber phase and the polymer matrix phase, thereby inhibiting interface debonding, delamination, and tearing, and improving the material's resistance to crack propagation and fatigue durability under long-term cyclic loading.
[0071] Beneficial effects:
[0072] 1. This invention uses pre-composite technology to form a continuous bonding interface between the reinforcing fiber phase and the polymer matrix phase. Then, through hot pressing, an interface transition layer is formed at the interface between the two phases. The interface bonding is strengthened through segment penetration, interpenetration and physical entanglement. This can effectively inhibit interface debonding, delamination and continuous crack propagation along the interface, and significantly improve the long-term interface stability and fatigue durability of fiber-reinforced polymer artificial valves.
[0073] 2. By controlling the hot-pressing temperature, pressure, and effective heat preservation time, this invention enables the polymer matrix phase to preferentially undergo interfacial penetration, while only the surface area of the reinforcing fiber phase is activated, and the internal main body maintains a continuous load-bearing structure. This can strengthen the interface while preserving the mechanical functions of both phases, thus taking into account both the structural enhancement and compliant opening and closing requirements of artificial valves.
[0074] 3. This invention can achieve interface enhancement without relying on complex chemical grafting or exogenous interface coupling agents, which can reduce the risk of exogenous reagent residue and interface layer detachment. The process is highly controllable, has good batch stability, and is suitable for large-scale production needs. Attached Figure Description
[0075] Figure 1 This is a comparative diagram of insufficient interface bonding and interface enhancement mechanism; the left side is a schematic diagram of the overall interface structure and failure behavior in the state of insufficient interface bonding / failure, the right side is a schematic diagram of the overall interface structure and force transmission and crack resistance behavior in the state of interface transition layer enhancement, and the enlarged partial images below correspond to the microscopic features of the interface and crack propagation mode in the two states respectively.
[0076] Figure 2A schematic diagram illustrating the material selection and interface formation principle for enhancing the relationship between the fiber phase and the polymer matrix phase; wherein ① is a schematic diagram of the chemical structure matching relationship, ② is a schematic diagram of the mechanical property matching relationship, ③ is a schematic diagram of the thermal transformation behavior matching relationship, and ④ is a schematic diagram of the chain segment movement and interface formation process.
[0077] Figure 3 The above diagram shows the preparation process and interface evolution of the fiber-reinforced polymer artificial valve interface reinforcement material; the upper part is a complete process flow diagram from the preparation of the reinforcing fiber phase to the final artificial valve molding, and the lower part is a structural evolution diagram of the interface transition layer from the pre-forming stage to the hot-pressing stage.
[0078] Figure 4 This is a schematic diagram comparing the failure modes of the material interface before and after hot pressing interface enhancement treatment; the left side is a schematic diagram of the failure modes of the material interface without temperature-controlled hot pressing treatment, and the right side is a schematic diagram of the force transmission and crack resistance modes of the material interface after temperature-controlled hot pressing treatment. Detailed Implementation
[0079] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0080] In the following text, the saline solution was purchased from Shandong Qidu Pharmaceutical Co., Ltd., and its brand name is Qidu Kelin.
[0081] The following are the test methods for relevant performance indicators in each embodiment or comparative example, the specific procedures for the relevant tests, and the methods for judging relevant phenomena:
[0082] Tensile modulus: Determined according to GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets" or ISO 527-3:2018. Samples are composite films or leaf-shaped materials with a thickness of less than 1 mm. Strip specimens are cut and conditioned at 23±2℃ and 50%±10% relative humidity for at least 24 hours before testing. Tensile testing is performed using a universal testing machine. The tensile modulus is calculated as the slope of the stress-strain curve within the strain range of 0.05%-0.25%. Instron 5943, Instron 5567, or equivalent universal testing machines can be used.
[0083] Tg: Determined by differential scanning calorimetry (DSC) according to GB / T 19466.2-2025 or ISO 11357-2:2020. The sample mass is 5-10 mg, and the test is conducted under a nitrogen atmosphere at a heating rate of 10 °C / min. The midpoint temperature of the glass transition region in the second heating curve is taken as Tg. The testing instrument can be a TA Instruments DSC Q2000, DSC 2500, or an equivalent differential scanning calorimeter. For polyurethane materials with indistinct glass transition in the hard segment, dynamic thermomechanical analysis can be further performed according to ISO 6721-11:2019, with the peak tanδ temperature or the midpoint temperature of the storage modulus abrupt change region taken as the corresponding Tg.
[0084] Ts: Ts is defined as the softening temperature at which the polymer matrix phase dominates interfacial penetration and segmental diffusion, and is determined using dynamic thermomechanical analysis. The test mode is either the stretch film mode or the three-point bending mode, with a frequency of 1 Hz, a heating rate of 3 °C / min, and a test atmosphere of nitrogen or air. Ts is defined as the initial temperature at which the storage modulus E′ begins to decrease rapidly with increasing temperature, determined by the intersection of the low-temperature plateau baseline and the tangent line of the maximum slope of the E′ descent segment. If the sample has a distinct melting peak, the melting peak initiation temperature measured by DSC can also be used as Ts, but the same Ts determination method should be used for the same set of control samples. The testing instrument can be a TA Instruments DMA Q800, DMA 850, or an equivalent dynamic thermomechanical analysis device.
[0085] 90° peel strength and interfacial peel strength: determined according to ASTM D6862-11 (2021). Samples are cut into strips 10 mm or 25 mm wide, with an unbonded section left at one end for peeling. Using a 90° peel clamp, the peel direction is maintained at approximately 90° to the bonded interface. The test is conducted at a peel speed of 50 mm / min, and the average peel force during the stable peeling phase is recorded. 90° peel strength is calculated by dividing the average peel force by the sample width, in N / mm. Interfacial peel strength is the average peel strength between the reinforcing fiber phase and the polymer matrix phase. Testing instruments can include an Instron 5943, Instron 5567, or an equivalent universal testing machine, equipped with a 90° peel clamp.
[0086] Tear strength: Measured using trouser-shaped tear test specimens. The specimens are cut into trouser shapes with a total width of 20 mm and a pre-cut length of 30 mm. The two trouser legs are clamped in the upper and lower fixtures of a universal testing machine and tested at a tensile speed of 50 mm / min at 23 ± 2℃. If a service environment needs to be simulated, the specimens can be tested immediately after soaking in physiological saline at 37℃ for 24 hours. The tearing energy is calculated by dividing the tearing energy obtained by integrating the force-displacement curve during the stable tearing stage by the newly formed fracture area. The newly formed fracture area is calculated as 2 × sample thickness × stable tear length. The stable tear length refers to the actual distance the crack extends from the start point to the end point of the stable plateau after the crack initiates at the pre-notch tip and continues to propagate along the predetermined longitudinal path of the specimen, corresponding to the tearing force-displacement curve entering the stable plateau stage. The start point of the stable plateau is the position where the moving average of the tearing force remains stable within a continuous crack propagation range of not less than 10 mm after the load rise or peak fluctuation at the moment of crack initiation. The end point of the stable plateau is the position before the crack reaches the end of the effective tearing zone, deviates from the predetermined tearing path, the specimen leg breaks, or a significant load change occurs due to the clamp or specimen edge. The stable tear length does not include the pre-notch length, the crack initiation stage, and the termination stage. It can be obtained by measuring the difference in crack position through specimen images or a ruler before and after the test, and the unit is kJ / m. 2 The testing instruments can be Instron 5943, Instron 5567, or equivalent universal testing machines.
[0087] Accelerated fatigue testing: The testing was conducted according to the principles of ISO 5840-1:2021 and applicable ISO 5840-2 or ISO 5840-3 regarding the durability evaluation of artificial heart valves. Samples were installed in an accelerated fatigue testing device for artificial heart valves. The circulating medium was 37°C physiological saline, the testing frequency was 20Hz, and the closure pressure differential was 100mmHg. Samples were taken or the device was stopped for observation after 50 million, 100 million, 200 million, and 400 million cycles. The testing instrument could be a ViVitro HiCycle, a Dynatek M6 HeartValve Durability Tester, or an equivalent accelerated fatigue testing system for artificial heart valves.
[0088] Pulsating flow test: Performed according to ISO 5840-1:2021 and applicable ISO 5840-2 or ISO 5840-3 methods for evaluating the in vitro hydrodynamic performance of artificial heart valves. The sample is installed in the pulsating flow testing system, with 37°C physiological saline as the circulating medium. Test conditions are: heart rate 70 bpm, cardiac output 5.0 L / min, mean aortic pressure 100 mmHg. Mean transvalvular pressure gradient, regurgitation percentage, and effective valve orifice area are recorded. The testing instrument can be the ViVitro PulseDuplicator System, ViVitro SuperPump, or an equivalent pulsating flow testing system.
[0089] Fatigue life: For samples after valve fabrication, fatigue life is defined as the number of cycles from the start of the test to the occurrence of any failure phenomenon such as macroscopic tearing, obvious delamination, obvious interface deadhesion, or leaflet function decline under accelerated fatigue testing conditions; if failure is not achieved after reaching the predetermined number of cycles, it is recorded as "not less than the number of cycles". Leaflet function decline refers to the unacceptable deterioration of the leaflet opening and closing motion or hemodynamic performance of the artificial valve relative to the pre-fatigue baseline after accelerated fatigue testing without the occurrence of macroscopic tearing, obvious delamination, or obvious interface deadhesion. Leaflet function decline is determined when any of the following conditions occur: (1) the average transvalvular pressure gradient increases by more than 10%; (2) the percentage of regurgitation increases by more than 10%; (3) the effective valve orifice area decreases by more than 10%; (4) in high-speed imaging or synchronous visualization observation for 10 consecutive pulse cycles, any leaflet shows persistent limited opening, incomplete closing, obvious asynchronous opening and closing, abnormal rollover, jamming, or irreversible permanent morphological abnormalities. The rate of change of the average transvalvular pressure gradient = (average transvalvular pressure gradient after fatigue - average transvalvular pressure gradient before fatigue) × 100% / average transvalvular pressure gradient before fatigue; the rate of change of the regurgitation percentage = (percentage of regurgitation after fatigue - percentage of regurgitation before fatigue) × 100% / percentage of regurgitation before fatigue; the rate of change of the effective valve orifice area = (effective valve orifice area before fatigue - effective valve orifice area after fatigue) × 100% / effective valve orifice area before fatigue.
[0090] Judgment of macroscopic tearing, obvious delamination, or obvious interfacial debonding: Macroscopic tearing is defined as a through-crack, leaflet edge crack, or continuous crack with a length of not less than 0.5 mm that can be observed with the naked eye or under a 10x stereomicroscope. Obvious delamination is defined as the presence of a gap between the reinforcing fiber layer and the polymer matrix layer with a length of not less than 1 mm or an area of not less than 1 mm². 2The continuous interlayer separation region. Obvious interfacial debonding is defined as the appearance of a continuous interfacial gap or fiber pull-out channel with a length of not less than 100 μm between the reinforcing fiber phase and the polymer matrix phase during stereomicroscopy, scanning electron microscopy, or cross-sectional microscopy. Observation instruments can include a Leica M205 C stereomicroscope, a Zeiss Axio Imager optical microscope, a Hitachi SU8010 scanning electron microscope, or equivalent equipment.
[0091] Determining whether the crack propagation path is continuous along the interface between the reinforcing fiber phase and the polymer matrix phase: After tearing, fracture, or fatigue testing, the crack area is observed using scanning electron microscopy, three-dimensional laser confocal microscopy, or optical microscopy. At least five fields of view are selected along the main crack path, and ImageJ or equivalent image analysis software is used to measure the proportion of the crack length propagating along the interface between the reinforcing fiber phase and the polymer matrix phase to the total crack length. If this proportion is not less than 50%, the crack is determined to mainly propagate continuously along the interface between the reinforcing fiber phase and the polymer matrix phase; if this proportion is less than 50%, and at least one of the following phenomena is observed: crack deflection, crack passivation, fiber bridging, or matrix / fiber co-fracture, the crack is determined not to mainly propagate continuously along the interface. Observation instruments can include a Zeiss LSM 980 three-dimensional laser confocal microscope, a Leica SP8 three-dimensional laser confocal microscope, a Hitachi SU8010 scanning electron microscope, or equivalent equipment.
[0092] The preparation process of the poly(carbonate-urea-polyurethane) is described below:
[0093] (1) Add polycarbonate glycol (manufacturer: Sigma-Aldrich, grade: 410706) to a reactor equipped with mechanical stirrer, nitrogen inlet, thermometer and dropping funnel, heat to 80°C and dehydrate under vacuum for 1 hour, then introduce dry nitrogen to restore the pressure inside the reactor to basically equal to the external atmospheric pressure, and maintain nitrogen protection.
[0094] (2) Cool the system to 70°C, add 4,4′-diphenylmethane diisocyanate, control the molar ratio of isocyanate group to hydroxyl group to be 1.98:1, add dibutyltin dilaurate, and react at 70°C for 2 h to obtain terminal isocyanate prepolymer.
[0095] (3) Dissolve 1,4-diaminobutane in anhydrous N,N-dimethylformamide to prepare a 1,4-diaminobutane solution with a mass concentration of 10 wt%; under nitrogen protection and at 10 °C, add the 1,4-diaminobutane solution dropwise to the terminal isocyanate prepolymer obtained in step (2), and after the addition is complete, react at 10 °C for 30 min, and then raise the temperature to room temperature for 2 h; wherein, the molar ratio of the amino group contained in 1,4-diaminobutane to the remaining isocyanate group in the prepolymer obtained in step (2) is controlled to be 1:1;
[0096] (4) After the reaction is completed, Fourier transform infrared spectroscopy or di-n-butylamine back titration method is used to detect the residual isocyanate groups in the system; when the characteristic absorption peak of isocyanate groups basically disappears, poly(carbonate-urea-polyurethane) reaction solution is obtained.
[0097] (5) Pour the reaction solution obtained in step (4) into a polytetrafluoroethylene tray, vacuum dry at 60°C for 12 hours, and then vacuum dry at 80°C for 24 hours to obtain transparent or light yellow poly(carbonate-urea-polyurethane) blocks.
[0098] The feed mass of dibutyltin dilaurate is 0.03 wt% of the total feed mass of polycarbonate diol, 4,4′-diphenylmethane diisocyanate and 1,4-diaminobutane.
[0099] The following describes the method for fabricating fiber-reinforced polymer artificial valves from interface-reinforced materials: The interface-reinforced material is cut at room temperature into three identical leaflet preforms using a leaflet cutting die matching the target valve specifications. Each leaflet preform includes a fixed area at the periphery and a movable leaflet area in the center; the fixed area is used to connect with the valve annulus, and the movable leaflet area must be free of perforations, creases, obvious delamination, continuous bubbles, or visible defects. For interface-reinforced materials with oriented fiber structures, the main fiber orientation is set along the circumference of the valve annulus or approximately parallel to the direction of the leaflet free edge during cutting; for random fiber mesh structures, the fiber mesh surface density, thickness, and cutting direction are recorded. The three leaflet preforms are then assembled onto a rigid valve annulus or valve testing fixture matching the nominal size of the target valve, with the three joints evenly spaced at 120° intervals along the circumference of the valve annulus. Each leaflet's fixing area is secured to the valve annulus using inner and outer pressure rings or equivalent mechanical fixing methods. The fixing structure should be located within the leaflet fixing area and should not encroach on the movable leaflet area, the free edge of the leaflet, or the leaflet mating area. After assembly, the three leaflets should form a continuous mating surface, and under no-pressure conditions, there should be no obvious twisting, wrinkling, local warping, or delamination of the fixing area. After assembly, the valve sample undergoes visual inspection and static opening and closing inspection. A qualified sample should meet the following requirements: each leaflet can open and close freely; the three leaflets form a continuous mating surface; the fixing area should be free of debonding, slippage, or material damage; and the movable leaflet area should be free of visible cracks, pinholes, continuous bubbles, and obvious interface delamination. Samples that fail the above inspections will not proceed to the pulsating flow test or accelerated fatigue test. Valve samples that pass the visual and static opening and closing inspections are immersed in physiological saline at 37°C for 24 hours before being placed in the pulsating flow test device or accelerated fatigue test device. Before fatigue testing, record initial hydrodynamic parameters such as average transvalvular pressure difference, backflow percentage, and effective valve area.
[0100] It should be noted that the parameter ranges and material selections described in this invention are effective implementation ranges derived from a large number of preliminary variable screening experiments. The following embodiments do not exhaustively list all feasible material ratios and process parameter combinations; only representative formulation systems and process conditions are selected for effect verification. This design is not intended to limit the scope of protection of this invention. Those skilled in the art can adjust any parameter based on the parameter ranges defined in this invention to achieve stable preparation of interface reinforcement materials for fiber-reinforced polymer artificial valves. These adjustments do not exceed the scope of protection defined by the appended claims.
[0101] The specific manufacturer information of the relevant substances disclosed in the various embodiments of this invention is merely for the purpose of fully disclosing the technical solution, facilitating understanding, reproduction, and verification of the technical effects by those skilled in the art, and is an exemplary description of the implementation methods, not a limitation on the scope of protection of this invention. Those skilled in the art should understand that, without departing from the core technical concept and substantive technical solution of this invention, similar equivalent raw materials produced by other manufacturers can be used to implement this invention. Such equivalent substitutions and conventional modifications all fall within the scope of protection of this invention, and the protection boundary of this invention should not be limited based on the specific manufacturer information recorded in the embodiments.
[0102] Example A1
[0103] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0104] (1) Preparation of materials;
[0105] Reinforcing fiber phase material: poly(carbonate-urea-polyurethane), tensile modulus of 25.0 MPa, Tg of 120℃;
[0106] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0107] Solvent b: Anhydrous tetrahydrofuran;
[0108] Polymer matrix material: siloxane-polycarbonate polyurethane, manufactured by DSM Biomedical, brand name CARBOSIL® 20-80A, tensile modulus of 12.3 MPa, Ts of 80℃;
[0109] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0110] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 12 hours at 25±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles, resulting in a spinning solution with a concentration of 0.10 g / mL; a 0.60 mm inner diameter needle is used to introduce the solution into an air-jet electrospinning device at a feed rate of 0.30 mL / h for spinning, thereby obtaining a reinforcing fiber phase with a fiber diameter of 300-500 nm; wherein, the spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 40℃, and the ambient humidity is 45%;
[0111] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b, and the mixture is magnetically stirred overnight at room temperature to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0112] (3) Pre-composite;
[0113] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0114] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0115] The hot pressing temperature is 210℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 10min;
[0116] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0117] (5) Cool the product from step (4);
[0118] The cooling termination temperature was 30℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0119] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 35%; a thickness of 200 μm (interfacial transition layer thickness of 0.9 μm); a 90° peel strength of 3.6 N / mm; an interfacial peel strength of 5.1 N / mm; and a tearing energy of 104 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37℃ physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsed flow test was carried out again after the accelerated fatigue test, the average transvalvular pressure difference change rate was 3.9%, the regurgitation percentage change rate was 4.6%, the effective valve area change rate was 3.4%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0120] Example A2
[0121] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0122] (1) Preparation of materials;
[0123] Reinforcing fiber phase material: poly(carbonate-urea-polyurethane), tensile modulus of 25.0 MPa, Tg of 120℃;
[0124] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0125] Solvent b: Anhydrous tetrahydrofuran;
[0126] Polymer matrix material: siloxane-polycarbonate polyurethane, manufactured by DSM Biomedical, brand name CARBOSIL®20-80A, tensile modulus of 12.3 MPa, Ts of 80℃;
[0127] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0128] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 12 hours at 25±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles, resulting in a spinning solution with a concentration of 0.10 g / mL; a 0.60 mm inner diameter needle is used to introduce the solution into an air-jet electrospinning device at a feed rate of 0.30 mL / h for spinning, thereby obtaining a reinforcing fiber phase with a fiber diameter of 300-500 nm; wherein, the spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 40℃, and the ambient humidity is 45%;
[0129] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b, and the mixture is magnetically stirred overnight at room temperature to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0130] (3) Pre-composite;
[0131] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0132] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0133] The hot pressing temperature is 200℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 10min;
[0134] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0135] (5) Cool the product from step (4);
[0136] The cooling termination temperature was 30℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0137] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 35%; a thickness of 30 μm (interfacial transition layer thickness of 0.6 μm); a 90° peel strength of 3.5 N / mm; an interfacial peel strength of 4.8 N / mm; and a tearing energy of 98 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37℃ physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsed flow test was carried out again after the accelerated fatigue test, the average transvalvular pressure difference changed by 4.2%, the regurgitation percentage changed by 5%, the effective valve area changed by 3.7%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0138] Comparative Example A1
[0139] A method for preparing a material differs from Example A2 only in that step (4) is omitted.
[0140] The final material exhibits a 90° peel strength of 1.2 N / mm, an interfacial peel strength of 1.7 N / mm, and a tear energy of 52 kJ / m. 2 The fatigue life is less than 400 million cycles; the fiber-reinforced polymer artificial valve made of the material, under accelerated fatigue test conditions of 37°C physiological saline, 20Hz frequency and closure pressure difference of 100mmHg, showed macroscopic tearing of the leaflet after 400 million cycles.
[0141] Compared to Example A2, Comparative Example A1 showed significantly worse 90° peel strength, interfacial peel strength, tearing energy, and fatigue stability. This is because, without hot-pressing interfacial reinforcement treatment, the polymer matrix phase mainly adheres to the surface of the reinforcing fiber phase through physical wetting and coating. The surface chain segments of the reinforcing fiber phase and the polymer matrix phase chain segments do not sufficiently form chain diffusion, physical entanglement, and intermolecular interactions, failing to form a continuous interfacial transition layer. Consequently, the interfacial force transmission capacity and anti-debonding ability are weak, resulting in a significant decrease in interfacial bonding strength and crack resistance, making it prone to failure under long-term cyclic loading.
[0142] Comparative Example A2
[0143] A method for preparing a material differs from Example A2 only in that: in step (4), the hot pressing temperature is 80°C.
[0144] The final material exhibits a 90° peel strength of 1.6 N / mm, an interfacial peel strength of 2.2 N / mm, and a tear energy of 57 kJ / m. 2 The fatigue life is less than 400 million cycles; the fiber-reinforced polymer artificial valve made of the material, under accelerated fatigue test conditions of 37°C physiological saline, 20Hz frequency and closure pressure difference of 100mmHg, showed obvious interfacial deadhesion of the leaflet after 400 million cycles.
[0145] Compared to Example A2, Comparative Example A2 exhibits significantly worse 90° peel strength, interfacial peel strength, tearing energy, and fatigue stability. This is because the hot-pressing temperature equals the softening temperature Ts of the polymer matrix phase, which dominates interfacial penetration. At 80°C, the melt viscosity of the polymer matrix phase segments remains high, making it difficult to fully penetrate the pores of the reinforcing fiber network. Furthermore, a continuous interfacial transition layer cannot be formed between the reinforcing fiber phase and the polymer matrix phase, significantly limiting segment diffusion, interpenetration, and physical entanglement at the interface. The resulting material primarily relies on physical wetting and surface coating for bonding, resulting in weak interfacial load transfer capacity. Cracks easily propagate continuously along the interface between the reinforcing fiber phase and the polymer matrix phase, thus significantly reducing the 90° peel strength, interfacial peel strength, and tearing energy. Under long-term cyclic loading, the interface is prone to debonding and delamination, resulting in a fatigue life below 400 million cycles. Significant interfacial debonding is observed after 400 million cycles.
[0146] Example A3
[0147] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0148] (1) Preparation of materials;
[0149] Reinforcing fiber phase material: poly(carbonate-urea-polyurethane), tensile modulus of 25.0 MPa, Tg of 120℃;
[0150] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0151] Solvent b: Anhydrous tetrahydrofuran;
[0152] Polymer matrix material: siloxane-polycarbonate polyurethane, manufactured by DSM Biomedical, brand name CARBOSIL®20-80A, tensile modulus of 12.3 MPa, Ts of 80℃;
[0153] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0154] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 12 hours at 25±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles, resulting in a spinning solution with a concentration of 0.10 g / mL; a 0.60 mm inner diameter needle is used to introduce the solution into an air-jet electrospinning device at a feed rate of 0.30 mL / h for spinning, thereby obtaining a reinforcing fiber phase with a fiber diameter of 300-500 nm; wherein, the spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 40℃, and the ambient humidity is 45%;
[0155] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b, and the mixture is magnetically stirred overnight at room temperature to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0156] (3) Pre-composite;
[0157] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0158] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0159] The hot pressing temperature is 200℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 10min;
[0160] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0161] (5) Cool the product from step (4);
[0162] The cooling termination temperature was 30℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0163] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 35%; a thickness of 1000 μm (interfacial transition layer thickness of 0.8 μm); a 90° peel strength of 3.6 N / mm; an interfacial peel strength of 4.9 N / mm; and a tearing energy of 100 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37°C physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsed flow test was performed again after the accelerated fatigue test, the average transvalvular pressure difference changed by 4%, the regurgitation percentage changed by 4.8%, the effective valve area changed by 3.5%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0164] Example A4
[0165] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0166] (1) Preparation of materials;
[0167] Reinforcing fiber phase material: poly(carbonate-urea-polyurethane), tensile modulus of 25.0 MPa, Tg of 120℃;
[0168] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0169] Solvent b: Anhydrous tetrahydrofuran;
[0170] Polymer matrix material: siloxane-polycarbonate polyurethane, manufactured by DSM Biomedical, brand name CARBOSIL®20-80A, tensile modulus of 12.3 MPa, Ts of 80℃;
[0171] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0172] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 12 hours at 25±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles, resulting in a spinning solution with a concentration of 0.10 g / mL; a 0.60 mm inner diameter needle is used to introduce the solution into an air-jet electrospinning device at a feed rate of 0.30 mL / h for spinning, thereby obtaining a reinforcing fiber phase with a fiber diameter of 300-500 nm; wherein, the spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 40℃, and the ambient humidity is 45%;
[0173] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b, and the mixture is magnetically stirred overnight at room temperature to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0174] (3) Pre-composite;
[0175] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0176] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0177] The hot pressing temperature is 200℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 10min;
[0178] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0179] (5) Cool the product from step (4);
[0180] The cooling termination temperature was 30℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0181] The final interface-reinforced material had a 5% volume fraction of reinforcing fiber phase; a thickness of 200 μm (with a 0.4 μm thickness of the interfacial transition layer); a 90° peel strength of 2.6 N / mm; an interfacial peel strength of 3.7 N / mm; and a tearing energy of 63 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37°C physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsating flow test was carried out again after the accelerated fatigue test, the average transvalvular pressure difference changed by 6.4%, the regurgitation percentage changed by 7.1%, the effective valve area changed by 5.9%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0182] Example A5
[0183] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0184] (1) Preparation of materials;
[0185] Reinforcing fiber phase material: poly(carbonate-urea-polyurethane), tensile modulus of 25.0 MPa, Tg of 120℃;
[0186] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0187] Solvent b: Anhydrous tetrahydrofuran;
[0188] Polymer matrix material: siloxane-polycarbonate polyurethane, manufactured by DSM Biomedical, brand name CARBOSIL® 20-80A, tensile modulus of 12.3 MPa, Ts of 80℃;
[0189] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0190] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 12 hours at 25±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles, resulting in a spinning solution with a concentration of 0.10 g / mL; a 0.60 mm inner diameter needle is used to introduce the solution into an air-jet electrospinning device at a feed rate of 0.30 mL / h for spinning, thereby obtaining a reinforcing fiber phase with a fiber diameter of 300-500 nm; wherein, the spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 40℃, and the ambient humidity is 45%;
[0191] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b, and the mixture is magnetically stirred overnight at room temperature to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0192] (3) Pre-composite;
[0193] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0194] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0195] The hot pressing temperature is 200℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 10min;
[0196] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0197] (5) Cool the product from step (4);
[0198] The cooling termination temperature was 30℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0199] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 80%; its thickness was 200 μm (the interfacial transition layer was 0.7 μm); its 90° peel strength was 3.3 N / mm; its interfacial peel strength was 4.7 N / mm; and its tear energy was 112 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37℃ physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsating flow test was carried out again after the accelerated fatigue test, the average transvalvular pressure difference change rate was 4.7%, the regurgitation percentage change rate was 5.6%, the effective valve area change rate was 4.1%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0200] Example A6
[0201] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0202] (1) Preparation of materials;
[0203] Reinforcing fiber phase material: poly(carbonate-urea-polyurethane), tensile modulus of 25.0 MPa, Tg of 120℃;
[0204] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0205] Solvent b: Anhydrous tetrahydrofuran;
[0206] Polymer matrix material: siloxane-polycarbonate polyurethane, manufactured by DSM Biomedical, brand name CARBOSIL® 20-80A, tensile modulus of 12.3 MPa, Ts of 80℃;
[0207] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0208] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 12 hours at 25±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles, resulting in a spinning solution with a concentration of 0.10 g / mL; a 0.60 mm inner diameter needle is used to introduce the solution into an air-jet electrospinning device at a feed rate of 0.30 mL / h for spinning, thereby obtaining a reinforcing fiber phase with a fiber diameter of 300-500 nm; wherein, the spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 40℃, and the ambient humidity is 45%;
[0209] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b, and the mixture is magnetically stirred overnight at room temperature to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0210] (3) Pre-composite;
[0211] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0212] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0213] The hot pressing temperature is 190℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 10min;
[0214] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0215] (5) Cool the product from step (4);
[0216] The cooling termination temperature was 30℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0217] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 35%; a thickness of 200 μm (with a 0.5 μm thickness of the interface transition layer); a 90° peel strength of 3.2 N / mm; an interfacial peel strength of 4.3 N / mm; and a tearing energy of 88 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37℃ physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsating flow test was carried out again after the accelerated fatigue test, the average transvalvular pressure difference changed by 5.2%, the regurgitation percentage changed by 6%, the effective valve area changed by 4.6%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0218] Example A7
[0219] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0220] (1) Preparation of materials;
[0221] Reinforcing fiber phase material: poly(carbonate-urea-polyurethane), tensile modulus of 25.0 MPa, Tg of 120℃;
[0222] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0223] Solvent b: Anhydrous tetrahydrofuran;
[0224] Polymer matrix material: siloxane-polycarbonate polyurethane, manufactured by DSM Biomedical, brand name CARBOSIL® 20-80A, tensile modulus of 12.3 MPa, Ts of 80℃.
[0225] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0226] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 12 hours at 25±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles, resulting in a spinning solution with a concentration of 0.10 g / mL; a 0.60 mm inner diameter needle is used to introduce the solution into an air-jet electrospinning device at a feed rate of 0.30 mL / h for spinning, thereby obtaining a reinforcing fiber phase with a fiber diameter of 300-500 nm; wherein, the spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 40℃, and the ambient humidity is 45%;
[0227] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b, and the mixture is magnetically stirred overnight at room temperature to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL.
[0228] (3) Pre-composite;
[0229] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0230] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0231] The hot pressing temperature is 200℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 10min.
[0232] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0233] (5) Cool the product from step (4);
[0234] The cooling termination temperature was 30℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0235] The final interface-reinforced material had a volume fraction of 35% for the reinforcing fiber phase; a thickness of 200 μm (interfacial transition layer thickness of 0.7 μm); a 90° peel strength of 3.5 N / mm; an interfacial peel strength of 4.9 N / mm; a tearing energy of 100 kJ / m²; and a fatigue life of at least 400 million cycles. The fiber-reinforced polymer artificial valve made from this interface-reinforced material, under accelerated fatigue testing conditions of 37°C physiological saline, 20 Hz frequency, and a closure pressure difference of 100 mmHg, showed no macroscopic tearing, significant delamination, or significant interfacial debonding after 400 million cycles. When subjected to pulsating flow testing after accelerated fatigue testing, the average transvalvular pressure difference changed by 4.1%, the regurgitation percentage changed by 4.9%, and the effective valve orifice area changed by 3.6%. The crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0236] Example B1
[0237] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0238] (1) Preparation of materials;
[0239] Reinforcing fiber phase material: polycarbonate-type polyurethane, manufactured by DSM Biomedical, brand name Bionate® 80A PCU, tensile modulus of 135MPa, Tg of 113℃;
[0240] Polymer matrix material: polyether ester block copolymer elastomer, manufactured by DuPont, brand name Hytrel®4056, with a tensile modulus of 60 MPa and a temperature range of 108°C.
[0241] Solvent a: A mixture of hexafluoroisopropanol and dimethylformamide in a volume ratio of 3:1;
[0242] Solvent b: A mixture of hexafluoroisopropanol and anhydrous tetrahydrofuran in a volume ratio of 7:3;
[0243] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0244] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 16 hours at 22±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles. A spinning solution with a concentration of 0.10 g / mL can be obtained at room temperature. Spinning is carried out using an air-jet electrospinning device with a needle with an inner diameter of 0.60 mm and a liquid inlet rate of 0.30 mL / h to obtain a reinforcing fiber phase with a fiber diameter of 300-500 nm. The spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 25℃, and the ambient humidity is 45%.
[0245] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0246] (3) Pre-composite;
[0247] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0248] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0249] The hot pressing temperature is 188℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 8min;
[0250] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0251] (5) Cool the product from step (4);
[0252] The cooling termination temperature is 40℃, the cooling pressure is 7MPa, the cooling time is 10min, and the cooling atmosphere is nitrogen.
[0253] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 35%; a thickness of 200 μm (with a 0.4 μm thickness of the interface transition layer); a 90° peel strength of 2.6 N / mm; an interfacial peel strength of 3.5 N / mm; and a tearing energy of 70 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37℃ physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsed flow test was performed again after the accelerated fatigue test, the average transvalvular pressure difference changed by 6.1%, the regurgitation percentage changed by 6.8%, the effective valve area changed by 5.3%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0254] Example B2
[0255] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0256] (1) Preparation of materials;
[0257] Reinforcing fiber phase material: polycarbonate, manufactured by Covestro, grade Makrolon® 2405, with a tensile modulus of 2400 MPa and a Tg of 144℃;
[0258] Polymer matrix material: polyether ester block copolymer elastomer, manufactured by DuPont, brand name Hytrel®5556, with a tensile modulus of 180 MPa and a temperature range of 75°C.
[0259] Solvent a: anhydrous tetrahydrofuran / dimethylformamide, volume ratio 7:3;
[0260] Solvent b: hexafluoroisopropanol / anhydrous tetrahydrofuran, volume ratio 7:3;
[0261] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0262] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 16 hours at 22±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles. A spinning solution with a concentration of 0.10 g / mL can be obtained at room temperature. Spinning is carried out using an air-jet electrospinning device with a needle with an inner diameter of 0.60 mm and a liquid inlet rate of 0.30 mL / h to obtain a reinforcing fiber phase with a fiber diameter of 300-500 nm. The spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 25℃, and the ambient humidity is 45%.
[0263] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0264] (3) Pre-composite;
[0265] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0266] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0267] The hot pressing temperature is 200℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 8min;
[0268] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0269] (5) Cool the product from step (4);
[0270] The cooling termination temperature is 40℃, the cooling pressure is 7MPa, the cooling time is 10min, and the cooling atmosphere is nitrogen.
[0271] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 35%; a thickness of 200 μm (interfacial transition layer thickness of 0.7 μm); a 90° peel strength of 3 N / mm; an interfacial peel strength of 4.2 N / mm; and a tearing energy of 88 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37℃ physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsating flow test was carried out again after the accelerated fatigue test, the average transvalvular pressure difference change rate was 4.9%, the regurgitation percentage change rate was 5.7%, the effective valve area change rate was 4.4%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
[0272] Comparative Example B1
[0273] A method for preparing a material, which differs from Example B2 only in that step (4) is omitted.
[0274] The final material exhibits a 90° peel strength of 1.1 N / mm, an interfacial peel strength of 1.6 N / mm, and a tear energy of 49 kJ / m. 2 The fatigue life is less than 400 million cycles; the fiber-reinforced polymer artificial valve made of the material, under accelerated fatigue test conditions of 37°C physiological saline, 20Hz frequency and closure pressure difference of 100mmHg, showed obvious interfacial deadhesion of the leaflet after 400 million cycles.
[0275] Compared to Example B2, Comparative Example B1 showed significantly worse 90° peel strength, interfacial peel strength, tearing energy, and fatigue stability. This is because, without hot-pressing interfacial reinforcement treatment, the polymer matrix phase mainly adheres to the surface of the reinforcing fiber phase through physical wetting and coating. The surface segments of the reinforcing fiber phase and the polymer matrix phase segments do not sufficiently form segment diffusion, physical entanglement, and intermolecular interactions, thus failing to form a stable interfacial transition layer. Consequently, the interfacial force transmission capacity and anti-debonding ability are weak, resulting in a significant decrease in interfacial bonding performance and long-term fatigue performance.
[0276] Example B3
[0277] A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, comprising the following specific steps:
[0278] (1) Preparation of materials;
[0279] Reinforcing fiber phase material: polysulfone, manufactured by Solvay, grade Udel® P-1700, tensile modulus of 2480MPa, Tg of 190℃;
[0280] Polymer matrix material: polyether ester block copolymer elastomer, manufactured by DuPont, brand name Hytrel®5556, with a tensile modulus of 180 MPa and a temperature range of 75°C.
[0281] Solvent a: dimethylformamide / anhydrous tetrahydrofuran, volume ratio 7:3;
[0282] Solvent b: hexafluoroisopropanol / anhydrous tetrahydrofuran, volume ratio 7:3;
[0283] (2) Preparation of solutions of reinforcing fiber phase and polymer matrix phase;
[0284] The preparation process of the reinforcing fiber phase is as follows: the reinforcing fiber phase material is dissolved in solvent a, and magnetically stirred for 16 hours at 22±2℃ under closed conditions until the system is clear, homogeneous and free of visible insoluble particles. A spinning solution with a concentration of 0.10 g / mL can be obtained at room temperature. Spinning is carried out using an air-jet electrospinning device with a needle with an inner diameter of 0.60 mm and a liquid inlet rate of 0.30 mL / h to obtain a reinforcing fiber phase with a fiber diameter of 300-500 nm. The spinning voltage is 16 kV, the receiving distance is 20 cm, the airflow speed is 2.0 L / min, the receiving roller speed is 800 rpm, the spinning environment temperature is 25℃, and the ambient humidity is 45%.
[0285] The preparation process of the polymer matrix phase solution is as follows: the polymer matrix phase material is dissolved in solvent b to obtain a polymer matrix phase solution with a concentration of 0.10 g / mL;
[0286] (3) Pre-composite;
[0287] First, the reinforcing fiber phase is collected and cut to form a pre-fiber felt. Then, the pre-fiber felt is immersed in a polymer matrix solution, and the immersion is repeated twice, 5 seconds each time. Subsequently, the pre-fiber felt impregnated with the polymer matrix solution is stacked and laid out. If necessary, polymer matrix solution is added between the layers. Finally, the stacked material is simultaneously subjected to vacuum degassing and infiltration treatment under a vacuum of 150 mbar for 15 minutes to allow the polymer matrix solution to fully penetrate into the pores of the fiber network and the gaps on the fiber surface. Then, it is dried at 50°C for 12 hours to remove the solvent, resulting in a pre-composite preform. Throughout the process, the volume fraction of the reinforcing fiber phase and the thickness of the pre-composite preform are controlled by adjusting the areal density of the pre-fiber felt, the number of layers, and the amount of polymer matrix solution.
[0288] (4) Hot pressing is performed on the pre-composite blank from step (3);
[0289] The hot pressing temperature is 200℃, the hot pressing pressure is 7MPa, and the effective hot pressing holding time is 8min;
[0290] During the hot pressing process, an interfacial transition layer is formed at the interface between the reinforcing fiber phase and the polymer matrix phase.
[0291] (5) Cool the product from step (4);
[0292] The cooling termination temperature was 40℃, the cooling pressure was 7MPa, the cooling time was 10min, and the cooling atmosphere was nitrogen.
[0293] The final interface-reinforced material had a reinforcing fiber phase volume fraction of 35%; a thickness of 200 μm (interfacial transition layer thickness of 0.6 μm); a 90° peel strength of 2.8 N / mm; an interfacial peel strength of 3.9 N / mm; and a tearing energy of 82 kJ / m. 2 The fatigue life is no less than 400 million cycles. Under accelerated fatigue testing conditions of 37℃ physiological saline, 20Hz frequency, and a closing pressure difference of 100mmHg, the fiber-reinforced polymer artificial valve made of interface reinforcement material showed no macroscopic tearing, obvious delamination, or obvious interface debonding after 400 million cycles. When the pulsating flow test was carried out again after the accelerated fatigue test, the average transvalvular pressure difference change rate was 5.4%, the regurgitation percentage change rate was 6.2%, the effective valve area change rate was 4.8%, and the crack propagation path did not continuously extend along the interface between the reinforcing fiber phase and the polymer matrix phase.
Claims
1. A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves, characterized in that, The specific process is as follows: First, the reinforcing fiber phase and the polymer matrix phase are pre-composite, so that the polymer matrix phase enters the pores and / or surface gaps of the reinforcing fiber phase, thereby forming a continuous bonding interface between the reinforcing fiber phase and the polymer matrix phase. Subsequently, the pre-composite material is subjected to hot pressing treatment, which softens, melts or activates chain segments at the interface of the polymer matrix phase and penetrates into the surface of the reinforcing fiber phase. At the same time, the reinforcing fiber phase is activated only in the surface area, locally swollen or locally micro-melted, while the internal main body of the reinforcing fiber phase maintains a continuous structure. Finally, the material is cooled under pressure while maintaining continuous bonding at the interface to obtain an interface-reinforced material.
2. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, The reinforcing fiber phase and the polymer matrix phase satisfy at least one of the following structural matching conditions: a. Both contain at least one identical chemical structural unit in their molecular chains; b. Both contain complementary chemical structural units that can form hydrogen bonds, dipole interactions, or ion-dipole interactions with each other; c. Both contain similar soft segments, similar hard segments, or similar crystalline segments that can undergo local mutual dissolution, segment diffusion, or crystalline region intercalation under hot pressing; The chemical structural units are selected from urethane bonds, urea bonds, ester bonds, amide bonds, ether bonds, carbonate bonds, siloxane segments, fluorocarbon segments, olefin segments, aromatic segments, or combinations thereof.
3. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, The tensile modulus of the reinforcing fiber phase is higher than that of the polymer matrix phase.
4. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 3, characterized in that, The tensile modulus of the reinforcing fiber phase is 1.5-20 times that of the polymer matrix phase.
5. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, The glass transition temperature (Tg) of the hard segments of the surface chain of the reinforcing fiber phase is higher than the softening temperature (Ts) of the polymer matrix phase, which dominates interfacial penetration and chain diffusion. The morphology retention ability of the reinforcing fiber phase under hot pressing is higher than that of the polymer matrix phase.
6. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 5, characterized in that, The difference between Tg and Ts is 5-120℃.
7. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, Under hot pressing, the reinforcing fiber phase and the polymer matrix phase have different but matching chain segment mobility capabilities, which allows the polymer matrix phase chain segments to diffuse to the surface of the reinforcing fiber phase, and the surface chain segments of the reinforcing fiber phase to participate in interfacial interpenetration, while the internal bulk of the reinforcing fiber phase still maintains a continuous reinforcing structure.
8. A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to any one of claims 1 to 7, characterized in that, The reinforcing fiber phase material is poly(carbonate-urea-polyurethane), the polymer matrix phase material is siloxane-polycarbonate-polyurethane, the hot pressing temperature is 190-210℃, the hot pressing pressure is 5-10MPa, and the effective hot pressing holding time is 3-15min. Alternatively, the reinforcing fiber phase material is polycarbonate-type polyurethane, the polymer matrix phase material is polyether ester block copolymer elastomer, the hot pressing temperature is 150-188℃, the hot pressing pressure is 2-12MPa, and the effective hot pressing holding time is 1-15min. Alternatively, the reinforcing fiber phase material is polyurethane, the polymer matrix phase material is polyurethane elastomer, the hot pressing temperature is 160-220℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min. Alternatively, the reinforcing fiber phase material is polyester, the polymer matrix phase material is polyester elastomer, the hot pressing temperature is 140-210℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min. Alternatively, the reinforcing fiber phase material is polyamide, the polymer matrix phase material is polyamide elastomer, the hot pressing temperature is 160-240℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min. Alternatively, the reinforcing fiber phase material is polyolefin, the polymer matrix phase material is polyolefin elastomer or polyolefin, the hot pressing temperature is 120-180℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min. Alternatively, the reinforcing fiber phase material is a fluoropolymer, the polymer matrix phase material is a fluoroelastomer or fluoropolymer, the hot pressing temperature is 180-280℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing time is 1-30min. Alternatively, the reinforcing fiber phase material is polycarbonate, the polymer matrix phase material is polycarbonate elastomer, the hot pressing temperature is 170-240℃, the hot pressing pressure is 2-15MPa, and the effective hot pressing holding time is 1-20min.
9. A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, The diameter of the reinforcing fiber phase is 50nm-100μm.
10. A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 9, characterized in that, The reinforcing fiber phase is a nanofiber network with a fiber diameter of 50-1000 nm; or, the reinforcing fiber phase is a micron-sized filament, fabric, or braided skeleton with a fiber diameter of 1-100 μm.
11. A method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, In interface-reinforced materials, the volume fraction of the reinforcing fiber phase is 5%-80%.
12. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, The thickness of the interface reinforcement material is 30-1000 μm.
13. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, The pre-composite process is as follows: the reinforcing fiber phase is immersed in a polymer matrix phase solution, dispersion or melt, followed by vacuum degassing and infiltration treatment, and then the solvent is removed to obtain the pre-composite preform.
14. The method for preparing an interface reinforcement material for fiber-reinforced polymer artificial valves according to claim 1, characterized in that, The 90° peel strength of the interface-reinforced material is 2.6-3.6 N / mm, and the interfacial peel strength is 3.5-5.1 N / mm. The tearing energy of interface-reinforced materials is 63-112 kJ / m. 2 Fatigue life of no less than 400 million cycles; After 400 million cycles of accelerated fatigue testing under conditions of 37°C physiological saline, 20Hz frequency, and a closing pressure difference greater than 100mmHg, the fiber-reinforced polymer artificial valve made of interface-reinforced material showed no macroscopic tearing, obvious delamination, or obvious interface deadhesion of the leaflet. When the pulsed flow test was performed again after the accelerated fatigue test, the change rate of the average transvalvular pressure difference, the backflow percentage and the effective valve area were all less than 10%, and the crack propagation path did not extend continuously along the interface between the reinforcing fiber phase and the polymer matrix phase.